Adhesion procedures for CAD/CAM indirect resin composite block: A new resin primer versus a conventional silanizing agent - Hagino, Ryosuke; Mine, Atsushi; Kawaguchi-Uemura, Asuka; Tajiri-Yamada, Yuko; Yumitate, Masahiro; Ban, Shintaro; Miura, Jiro; Matsumoto, Mariko; Yatani, Hirofumi; Nakatani, Hayaki (Journal of prosthodontic research, 2020)
The purpose of this study was to evaluate the effectiveness of both a resin primer containing methyl methacrylate (MMA) and a silanizing agent on bonding to indirect resin composite blocks, using two types of build-up hybrid resin composites. SHOFU BLOCK HC (Shofu) specimens were blasted with alumina, after which one of two surface treatments was applied: CERA RESIN BOND (Shofu, the Silane group) or HC primer (Shofu, the MMA group). Resin composites made using either Solidex Hardura (SDH, Shofu) or Ceramage Duo (CMD, Shofu) were built up and micro-tensile bond strength (μTBS) values were measured after storage in water for either 24h or 6 months (n=24 per group). The fracture surfaces after μTBS measurements and the resin block/build-up resin interfaces were observed by scanning electron microscopy (SEM). The bond strength of the Silane/SDH group significantly decreased after 6 months (p<0.001), whereas in the MMA group there was no significant loss after 24h or 6 months (p=0.99). In the CMD group, the bond strength after 6 months was significantly lowered in both the Silane group (p<0.001) and the MMA group (p<0.001), but the latter still showed greater adhesion. SEM images demonstrated that the matrix resin was partially destroyed at the fracture surfaces of the MMA group and fracture surface unevenness was observed. A primer containing MMA produced stronger bonding to CAD/CAM resin even after long-term aging compared to a silane treatment.